ON THE VARIANCE OF LOCAL STEREOLOGICAL VOLUME ESTIMATORS - Jensen, Eva B Vedel (Image Analysis and Stereology, 2011)
In the present paper, the variance of local stereological volume estimators is studied. For isotropic designs, the variance depends on the shape of the body under study and the choice of reference point. It can be expressed in terms of an equivalent star body. For a collection of triaxial ellipsoids the variance is determined by simulation. The problem of estimating particle size distributions from central sections through the particles is also discussed.